2021
DOI: 10.1371/journal.pone.0248627
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ perceptions and motivations during the COVID-19 pandemic

Abstract: Background There has been a rapid increase in the number of cases of COVID-19 in Latin America, Africa, Asia and many countries that have an insufficient number of physicians and other health care personnel, and the need for the inclusion of medical students on health teams is a very important issue. It has been recommended that medical students work as volunteers, undergo appropriate training, not undertake any activity beyond their level of competence, and receive continuous supervision and adequate personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
83
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 16 publications
(22 reference statements)
3
83
0
4
Order By: Relevance
“…A study conducted among medical students in Brazil revealed that the sense of purpose or duty, which reflects the moral values linked to the medical profession, was the most important factor that influenced medical students’ desire to work during the COVID-19 pandemic. 21 Similarly, in the present study, almost all medical students reported that they have a responsibility to contribute to the COVID-19 health sector response in Sri Lanka, which indirectly highlights their academic and moral obligation. Further, it is important to note that irrespective of the academic year, all medical students were of a similar opinion.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…A study conducted among medical students in Brazil revealed that the sense of purpose or duty, which reflects the moral values linked to the medical profession, was the most important factor that influenced medical students’ desire to work during the COVID-19 pandemic. 21 Similarly, in the present study, almost all medical students reported that they have a responsibility to contribute to the COVID-19 health sector response in Sri Lanka, which indirectly highlights their academic and moral obligation. Further, it is important to note that irrespective of the academic year, all medical students were of a similar opinion.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, the self-perception of competence is reported as one of the leading factors influencing medical students’ motivation to engage in health-care activities during the COVID-19 pandemic. 21 This finding highlights that students can be better integrated into health-care teams by recognizing their meaningful contribution from the first year to the final year. Thus, medical education needs to identify value-added roles for medical students across different levels of academic training in order to combine learning with meaningful contributions to patient care and the health sector.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Existing literature on the intention of medical students to participate in COVID-19 prevention activities has investigated the correlation between other factors and intention to participate. A study on Chinese medical students cited pressure and the extent of support from family as correlating factors (7), while others found sense of purpose (25,26), desire to help (8,25), and to learn and gain professional experience (8,27) to be some of the most common reason for medical students to participate in frontline COVID-19 prevention activities. Knowing the possible influence of source of knowledge about COVID-19 on the intention of participation of nursing students implies that such intention can be encouraged by managing the content of information distributed through official (Ministry of Health) and community channels.…”
Section: Discussionmentioning
confidence: 99%
“…Nishimura et al showed high levels of stress amongst Japanese medical students in response to shift to online teaching [23]. Tempski et al reported in their extensive survey on Brazilian medical students that they were highly motivated by their sense of duty and professionalism rather than keenness to learn, to participate in the pandemic [24].…”
Section: Discussionmentioning
confidence: 99%